2004
DOI: 10.1111/j.1365-2273.2004.00783.x
|View full text |Cite
|
Sign up to set email alerts
|

Hearing thresholds in patients affected by rheumatoid arthritis

Abstract: Hearing thresholds in patients affected by rheumatoid arthritis The aim of the study was to evaluate hearing thresholds in 38 patients with rheumatoid arthritis, divided according to disease activity into active (group A, n = 20) and non‐active (group B, n = 18) patients. Pure tone audiometry, tympanometry and complete rheumatological assessment were performed. All patients presented poorer auditory thresholds compared with controls. Patients of group A had both air and bone conduction thresholds poorer than g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
3
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 15 publications
(16 reference statements)
5
24
3
2
Order By: Relevance
“…The DAS disease activity score was higher in cases of RA with hypoacusia. Those results are consistent with some literature data [4,9,16,17,21]. Takatsu et al detected statistical significant correlations between the degree of hearing loss and the plasma concentrations of interleukin 6 and metalloproteinase [10].…”
Section: Disscussionsupporting
confidence: 82%
“…The DAS disease activity score was higher in cases of RA with hypoacusia. Those results are consistent with some literature data [4,9,16,17,21]. Takatsu et al detected statistical significant correlations between the degree of hearing loss and the plasma concentrations of interleukin 6 and metalloproteinase [10].…”
Section: Disscussionsupporting
confidence: 82%
“…128 A histological study of rheumatoid arthritis has also suggested malleo-incudal and incudo-stapedial joint involvement, 129 and the expected increase in stiffness of the middle ear has been documented. [130][131][132][133] In contrast, other studies have found a decrease in stiffness, 134,135 but this could relate to changes in other parts of the ear, such as the tympanic membrane 134 or the joint capsules and ligaments. 133 Small conductive and sensorineural hearing losses have been reported in a proportion of patients with rheumatoid arthritis.…”
Section: Flexibility and Pressure-bufferingmentioning
confidence: 48%
“…133 Small conductive and sensorineural hearing losses have been reported in a proportion of patients with rheumatoid arthritis. 132,[136][137][138] It has been suggested that the sensorineural hearing impairment may be due to an increase in compressive force on the labyrinth, 131 perhaps due to a relative inability to buffer static pressure changes. However, alternative hypotheses include the effects of systemic neuritis, vasculitis or salicylate toxicity.…”
Section: Flexibility and Pressure-bufferingmentioning
confidence: 99%
“…[19] otoimmun hastalığı olan kişilerde iç kulağın durumunu incelemişler ve RA'lı hastalarda bilateral progresif sensorinöral işitme kaybı olduğunu tespit etmişlerdir. İşitme kayıpları genellikle SN tipte işitme kaybı olarak bildirilse de, birçok çalışmada SN ve iletim tipi işitme kaybının sıklıkla birlikte olduğu vurgulanmaktadır [4,9,10,15,20]. Literatüre benzer şekilde bu ça-lışmada da, RA'lı hasta grubumuzda iletim tipi işitme kaybının anlamlı olarak daha fazla olduğu, kemik yolu iletiminin ise özellikle yüksek frekanslarda ve kısmen etkilendiği ve sonuçta hem iletim tipi hem de SN tip işitme kayıpları olduğu görüldü.…”
Section: Discussionunclassified
“…[23] hastalığın aktif döneminde, yüksek frekanslarda işitme kaybının fazla olduğunu göstermiştir. Bu yayınlara rağmen birçok çalışmada ise, herhangi bir korelasyon olmadığı bildirilmiştir [20][21][22][23][24][25]. Bizim çalışmamızda da; hastaların RF pozitifliği, şiş eklem sayısı, sedimantasyon ve CRP değerleri ile işitme kaybı arasında herhangi bir ilişki saptanmamıştır.…”
Section: Discussionunclassified